Insights into the role of long non-coding RNAs in DNA methylation mediated transcriptional regulation - Yang, Zhen; Xu, Feng; Teschendorff, Andrew E.; Zhao, Yi; Yao, Lei; Li, Jian; He, Yungang (Frontiers in Molecular Biosciences, 2022)
DNA methylation is one of the most important epigenetic mechanisms that governing regulation of gene expression, aberrant DNA methylation patterns are strongly associated with human malignancies. Long non-coding RNAs (lncRNAs) have being discovered as a significant regulator on gene expression at the epigenetic level. Emerging evidences have indicated the intricate regulatory effects between lncRNAs and DNA methylation. On one hand, transcription of lncRNAs are controlled by the promoter methylation, which is similar to protein coding genes, on the other hand, lncRNA could interact with enzymes involved in DNA methylation to affect the methylation pattern of downstream genes, thus regulating their expression. In addition, circular RNAs (circRNAs) being an important class of noncoding RNA are also found to participate in this complex regulatory network. In this review, we summarize recent research progress on this crosstalk between lncRNA, circRNA, and DNA methylation as well as their potential functions in complex diseases including cancer. This work reveals a hidden layer for gene transcriptional regulation and enhances our understanding for epigenetics regarding detailed mechanisms on lncRNA regulatory function in human cancers.